Impact of ventricular tachycardia ablation in subcutaneous implantable cardioverter defibrillator carriers: a multicentre, international analysis from the iSUSI project - Schiavone, Marco; Gasperetti, Alessio; Compagnucci, Paolo; Vogler, Julia; Laredo, Mikael; Montemerlo, Elisabetta; Gulletta, Simone; Breitenstein, Alexander; Ziacchi, Matteo; Martinek, Martin; Casella, Michela; Palmisano, Pietro; et al. (Europace, 2024)
Catheter ablation (CA) of ventricular tachycardia (VT) has become an important tool to improve clinical outcomes in patients with appropriate transvenous implantable cardioverter defibrillator (ICD) shocks. The aim of our analysis was to test whether VT ablation (VTA) impacts long-term clinical outcomes even in subcutaneous ICD (S-ICD) carriers.International Subcutaneous Implantable Cardioverter Defibrillator (iSUSI) registry patients who experienced either an ICD shock or a hospitalization for monomorphic VT were included in this analysis. Based on an eventual VTA after the index event, patients were divided into VTA+ vs. VTA− cohorts. Primary outcome of the study was the occurrence of a combination of device-related appropriate shocks, monomorphic VTs, and cardiovascular mortality. Secondary outcomes were addressed individually. Among n = 1661 iSUSI patients, n = 211 were included: n = 177 experiencing ICD shocks and n = 34 hospitalized for VT. No significant differences in baseline characteristics were observed. Both the crude and the yearly event rate of the primary outcome (5/59 and 3.8% yearly event rate VTA+ vs. 41/152 and 16.4% yearly event rate in the VTA−; log-rank: P value = 0.0013) and the cardiovascular mortality (1/59 and 0.7% yearly event rate VTA+ vs. 13/152 and 4.7% yearly event rate VTA−; log-rank P = 0.043) were significantly lower in the VTA + cohort. At multivariate analysis, VTA was the only variable remaining associated with a lower incidence of the primary outcome [adjusted hazard ratio 0.262 (0.100-0.681), P = 0.006].In a real-world registry of S-ICD carriers, the combined study endpoint of arrhythmic events and cardiovascular mortality was lower in the patient cohort undergoing VTA at long-term follow-up.NCT0473876.